Multicentre, randomized comparison of two-stent and provisional stenting techniques in patients with complex coronary bifurcation lesions: the DEFINITION II trial. (26th June 2020) - Zhang, Jun-Jie; Ye, Fei; Xu, Kai; Kan, Jing; Tao, Ling; Santoso, Teguh; Munawar, Muhammad; Tresukosol, Damras; Li, Li; Sheiban, Imad; Li, Feng; Tian, Nai-Liang; et al.
Abstract: Aim: The present study aimed to assess the benefits of two-stent techniques for patients with DEFINITION criteria-defined complex coronary bifurcation lesions. Methods and results: In total, 653 patients with complex bifurcation lesions at 49 international centres were randomly assigned to undergo the systematic two-stent technique (two-stent group) or provisional stenting (provisional group). The primary endpoint was the composite of target lesion failure (TLF) at the 1-year follow-up, including cardiac death, target vessel myocardial infarction (TVMI), and clinically driven target lesion revascularization (TLR). The safety endpoint was definite or probable stent thrombosis. At the 1-year follow-up, TLF occurred in 37 (11.4%) and 20 (6.1%) patients in the provisional and two-stent groups, respectively [77.8%: double-kissing crush; hazard ratio (HR) 0.52, 95% confidence interval (CI) 0.30–0.90; P = 0.019], largely driven by increased TVMI (7.1%, HR 0.43, 95% CI 0.20–0.90; P = 0.025) and clinically driven TLR (5.5%, HR 0.43, 95% CI 0.19–1.00; P = 0.049) in the provisional group. At the 1 year after indexed procedures, the incidence of cardiac death was 2.5% in the provisional group, non-significant to 2.1% in the two-stent group (HR 0.86, 95% CI 0.31–2.37; P = 0.772). Conclusion: For DEFINITION criteria-defined complex coronary bifurcation lesions, the systematic two-stent approach was associated with a significant improvement in clinical outcomes compared with the provisional stenting approach. Further study is urgently warranted to identify the mechanisms contributing to the increased rate of TVMI after provisional stenting. Study registration: http://www.clinicaltrials.com ; Identifier: NCT02284750. Graphical Abstract: